WORKS OF ART AS AN OBJECT OF ENSURING INTEGRATION OF NATIONS - Hurriyat Karimberdievna, Khudoiberdieva (International Journal of Psychosocial Rehabilitation, 2020)
The article reflects the philosophical and aesthetic significance of the Uzbek people in the transfer of original works of art based on the centuries-old national mentality that have coexisted with different peoples for centuries.The idea of the nation is reflected in the works of their ancestors, including music, literature, art, visual arts, folk crafts and crafts, as well as their role in ensuring interethnic harmony in society.It reflects the development of modern Uzbek works of art based on the culture, national values, traditions and customs of peoples, which promote interethnic harmony in all spheres of public life, promote sustainable development, which protects the interests of various peoples and promotes peace in the country.The first of five initiatives put forward by the President of the country was the analysis of issues of increasing youth interest in a number of literature, art, music, theater and art.As part of this initiative, it is important to acquaint young people with applied art and Uzbek culture, strengthen their love of literature and art, increase the variety of theater productions, documentaries and films, and regularly visit museums and art exhibitions of our country.